Gating and the Need for Sleep: Dissociable Effects of Adenosine A1 and A2A Receptors - Lazarus, Michael; Oishi, Yo; Bjorness, Theresa E.; Greene, Robert W. (Frontiers in Neuroscience, 2019)
Roughly one-third of the human lifetime is spent in sleep, yet the reason for sleep remains unclear. Understanding the physiologic function of sleep is crucial toward establishing optimal health. Several proposed concepts address different aspects of sleep physiology, including humoral and circuit-based theories of sleep-wake regulation, the homeostatic two-process model of sleep regulation, the theory of sleep as a state of adaptive inactivity, and observations that arousal state and sleep homeostasis can be dissociated in pathologic disorders. Currently, there is no model that places the regulation of arousal and sleep homeostasis in a unified conceptual framework. Adenosine is well known as a somnogenic substance that affects normal sleep-wake patterns through several mechanisms in various brain locations via A1 or A2A receptors (A1Rs or A2ARs). Many cells and processes appear to play a role in modulating the extracellular concentration of adenosine at neuronal A1R or A2AR sites. Emerging evidence suggests that A1Rs and A2ARs have different roles in the regulation of sleep. In this review, we propose a model in which A2ARs allow the brain to sleep, i.e., these receptors provide sleep gating, whereas A1Rs modulate the function of sleep, i.e., these receptors are essential for the expression and resolution of sleep need. In this model, sleep is considered a brain state established in the absence of arousing inputs.